استراتيجية ادارة الفرص والتهديدات لتحقيق التنمية المستدامة بالمعاهد الفنية المتوسطة حالة دراسية مقابلة مع السيد مدير ادارة مكتب المعاهد الفنية المتوسطة ببلدية مصراته (Comprehensive Journal of Science, 2025)
The study aimed to identify the challenges and opportunities facing the administration of the Office of Intermediate Technical Institutes in Misrata Municipality in achieving sustainable development. The fourth element refers to quality education through management practices and their applications for trainees, taking into account gender equality (male and female students).The researchers used a descriptive analytical approach using data extracted from the records of the Administration of Intermediate Technical Institutes in Misrata Municipality, including the number of technical institutes within the municipality's administrative jurisdiction, which were appropriately distributed in line with population density. They also conducted an interview with the Director of the Administration of Intermediate Technical Institutes in the municipality. The interview questions revolved around the study topic and consisted of six different axes.The study concluded that there are several opportunities that the administration of the institutes can seek to achieve, through partnerships with industrial, production, and administrative companies in the municipality to improve their outputs for the labor market. Furthermore, the diversity of engineering specializations contributes to the diversity of graduates entering the labor market, both male and female. Among the challenges facing the administration of the institutes are the inadequacy of curricula to reflect technological and technical progress, and the obsolescence of the machinery and equipment available. The study recommended working to change the societal perception of intermediate technical education graduates by using the media, conferences, and workshops targeting community groups. It also recommended working to issue and implement laws and regulations specific to intermediate technical education, and encouraging graduates to establish their own projects through financial and advisory support from the state.